Employers' selection skills in recruiting fresh engineering graduates - Md Yusoff Y.; Zaharim A.; Omar M.Z.; Mohamed A.; Muhamad N.; Mustafa R. (2023)
The purpose of this paper is to observe employers' selection skills needed in recruiting fresh engineering graduates for their workforce. This study consists of a survey on engineering employ-ability skills which should be owned by graduates or new engineers hired by employers in Selangor, Malaysia. The questionnaire method has been chosen in order to determine the importance of engineering employ-ability skills possessed by new engineers. The skills were measured using 5-Likert scales and the level of importance of employ-ability skills were analysed by statistical mean. The finding shows the priority of employ-ability skills that employers would look for when evaluating and selecting new engineers. This paper examines the skills that affect the selection of new engineers and employers' point of view towards recruiting new engineer in Malaysia. Hopefully, this will help the employers' decision making on selecting the right candidate for an engineering post in their organisation. Engineering graduates also benefited from this paper as their preparation to enter the working world. The respondents of the survey are employers in a limited geographical area of Malaysia and only those in higher position in organization who have the autonomy to hire new engineers for the organization, familiar to project and know what kind of employ-ability skills needed in the future for the organisation, and knowledgeable on skills needed for engineers to operate necessary equipment successfully. 2009 IEEE.